2005
DOI: 10.1002/ajmg.a.30878
|View full text |Cite
|
Sign up to set email alerts
|

Michels syndrome, Carnevale syndrome, OSA syndrome, and Malpuech syndrome: Variable expression of a single disorder (3MC syndrome)?

Abstract: We report on a 3‐year‐old girl with Michels syndrome, a rare condition characterized by craniosynostosis, blepharophimosis, ptosis, epicanthus inversus, cleft lip/palate, abnormal supra‐umbilical abdominal wall, and mental deficiency. The phenotypic findings are compared with the six previously reported Michels cases, and with patients referred to as Carnevale, OSA, and Malpuech syndromes. Michels syndrome is characterized by cleft lip and palate, anterior chamber anomalies, blepharophimosis, epicanthus invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 13 publications
4
50
0
Order By: Relevance
“…We are not convinced that case 2 and 3 of the Kerstjens-Frederikse et al [2005] report have Malpuech syndrome, but we lack sufficient data to be sure about the latter and therefore followed the authors and included the patients. Six patients have been reported with Michels syndrome [Michels et al, 1978;Cunniff and Jones, 1990;De La Paz et al, 1991;Titomanlio et al, 2005]. We have kept the patient reported by Guion-Almeida and Rodini [1995] separately however, as in our opinion this patient resembles the patients reported by Carnevale et al [1989] and Mingarelli et al [1996] much more than those reported as having Michels syndrome.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We are not convinced that case 2 and 3 of the Kerstjens-Frederikse et al [2005] report have Malpuech syndrome, but we lack sufficient data to be sure about the latter and therefore followed the authors and included the patients. Six patients have been reported with Michels syndrome [Michels et al, 1978;Cunniff and Jones, 1990;De La Paz et al, 1991;Titomanlio et al, 2005]. We have kept the patient reported by Guion-Almeida and Rodini [1995] separately however, as in our opinion this patient resembles the patients reported by Carnevale et al [1989] and Mingarelli et al [1996] much more than those reported as having Michels syndrome.…”
Section: Discussionmentioning
confidence: 74%
“…These syndromes include Malpuech syndrome, Michels syndrome, Carnevale syndrome, OSA syndrome, and Mingarelli syndrome, and some include Juberg-Hayward syndrome as well. Titomanlio et al [2005] have suggested that the entities are in fact part of the same entity, and have proposed to name this 3MC The proband, a 4.5 year-old boy, was referred because of a progressive torticollis. He was the second-born child of healthy, consanguineous (first cousins) parents.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies recently revealed that mutations in MASP1 and COLEC11 underlie the etiology of 3MC syndrome (16), a rare autosomal recessive disorder characterized by facial dysmorphism, short stature, intellectual disability, midline defects, and caudal appendage (17,18). The common denominator of causative MASP1 gene defects is the absence of a functional form of MASP-3, but in one individual a nonsense mutation was localized to the part of MASP1 encoding the common domains of MASP-1, MASP-3, and MAp44, most likely conferring a complete deficiency of these proteins in the homozygous state ( Fig.…”
mentioning
confidence: 99%
“…However, partial overlap is evident with Michels, Carnevale, Malpuech, and OSA syndromes [Michels et al, 1978;Malpuech et al, 1983;Carnevale et al, 1989;Mingarelli et al, 1996], which are now considered a single entity [Titomanlio et al, 2005]; however, not all authors agree with this hypothesis [Al Kaissi et al, 2007]. These conditions all comprise specific eyelid anomalies (i.e., blepharoptosis, blepharophimosis, and epicanthus inversus) with hypertelorism.…”
Section: Discussionmentioning
confidence: 99%